Effects of red dragon fruit peel extract on tomato storage - Inna M. Rumainum; Zali Natalia Tiblolab (Agrotek, 2019)
The aim of this study was to identify the effects of the peel extract of red dragon fruit on the quality of tomato fruit during storage. Twenty one tomato fruits were immerced in the peel extract with concentrations of 0% (T0), 25% (T1), 50% (T2) and 100% (T3), where T0 to T3 represented the various treatment groups. Three fruits in each treatment were then randomly selected every two days, for quality analysis. The results showed that fruits from group T3 experienced lower weight loss when compared to T0, T1 and T2. Furthermore, there was no significant difference in the total soluble solids, and this indicates that the extract had no effect on fruit sweetness. Interestingly, fruits from T3 did not show any damage caused by fungus. In conclusion, the extract of red dragon fruit peel has antioxidant potential, which can be useful for food storage.